Long-Term Impact of Interprofessional Medical Mission Service Trips in Sierra Leone - Tran, Yen; Jarrett, Jennie; Gardner, Scott; Fernando, James; Milliron, Mark; Hong, Lisa (Frontiers in Medicine, 2021)
Objective: The purpose of this study was to evaluate the impact of capacity-building short-term mission service trips to Sierra Leone on local health education and perspectives. Methods: This was a prospective, mixed-methods study. During three mission trips between June 2017 and December 2019, health professional students taught multiple locally selected patient care-related topics. Local staff completed knowledge questionnaires and were surveyed or interviewed on mission service impact along with the cultural competence of missionaries. Mission team members completed the Intercultural Effectiveness Scale (IES) and surveys to determine their cultural competence. Results: After initial education, 90% passed the knowledge questionnaire with at least a 50% and the correct response rate was 57.9% versus 66.7% after 6 months and 2.5 years, respectively (p=0.40). Local staff ranked education/training as most valuable (84%) and highly desired (53%). Mean IES score and survey responses of both missionaries and local staff rated mission team cultural competence as average. Conclusions: Education-focused mission trips in Sierra Leone seem to have long-lasting benefits and a positive impact on local staff, though improved intercultural competence is needed.